The Use of Induced Pluripotent Stem Cells to Study the Effects of Adenosine Deaminase Deficiency on Human Neutrophil Development - Tsui, Michael; Min, Weixian; Ng, Stephanie; Dobbs, Kerry; Notarangelo, Luigi D.; Dror, Yigal; Grunebaum, Eyal (Frontiers in Immunology, 2021)
Inherited defects that abrogate the function of the adenosine deaminase (ADA) enzyme and consequently lead to the accumulation of toxic purine metabolites cause profound lymphopenia and severe combined immune deficiency. Additionally, neutropenia and impaired neutrophil function have been reported among ADA-deficient patients. However, due to the rarity of the disorder, the neutrophil developmental abnormalities and the mechanisms contributing to them have not been characterized. Induced pluripotent stem cells (iPSC) generated from 2 unrelated ADA-deficient patients and from healthy controls were differentiated through embryoid bodies into neutrophils. ADA deficiency led to a significant reduction in the number of all early multipotent hematopoietic progenitors. At later stages of differentiation, ADA deficiency impeded the formation of granulocyte colonies in methylcellulose cultures, leading to a significant decrease in the number of neutrophils generated from ADA-deficient iPSCs. The viability and apoptosis of ADA-deficient neutrophils isolated from methylcellulose cultures were unaffected, suggesting that the abnormal purine homeostasis in this condition interferes with differentiation or proliferation. Additionally, there was a significant increase in the percentage of hyper-lobular ADA-deficient neutrophils, and these neutrophils demonstrated significantly reduced ability to phagocytize fluorescent microspheres. Supplementing iPSCs and methylcellulose cultures with exogenous ADA, that can correct adenosine metabolism, reversed all abnormalities, cementing the critical role of ADA in neutrophil development. Moreover, chemical inhibition of the ribonucleotide reductase (RNR) enzyme, using hydroxyurea or a combination of nicotinamide and trichostatin A in iPSCs from healthy controls led to abnormal neutrophil differentiation similar to that observed in ADA deficiency, implicating RNR inhibition as a potential mechanism for the neutrophil abnormalities. In conclusion, the findings presented here demonstrate the important role of ADA in the development and function of neutrophils while clarifying the mechanisms responsible for the neutrophil abnormalities in ADA-deficient patients.